USING MICROSOFT SWAY IN IMPROVING ONLINE LEARNING: A CASE OF THE FOURTH GRADERS OF SDN BUBUTAN III/71 SURABAYA - Nurhayati, Titis; Sulistyowati, Reni (Acitya Wisesa: Journal of Multidisciplinary Research, 2022)
The objective of this research is to improve student learning outcomes by using Microsoft Sway media for class IV-A at SDN Bubutan III/71 Surabaya. The research method used is classroom action research and the research subjects are students of class IV-A SDN Bubutan III/71 Surabaya with total of 34 children. The data collection techniques in this research is using tests which all are combined in quantitative descriptive. The results of this research indicated that the application of Microsoft Sway media in the online learning for class IV-A is conducted through 2 cycles by using test techniques which had increased in their learning outcomes. This is attested by the acquisition of student scores before-after using Microsoft Sway. The first cycle activities before using Microsoft Sway media, from the total assessed of 34 students, only 20 students or 58.82% who can complete the KKM and for the rest of 14 students or 41.18% who cannot complete the KKM. Furthermore, the second cycle was implemented to them and student learning outcomes increased, from 34 students, there were 30 students or 88.24% who completed the KKM and 4 other students or 11.76% who cannot complete the KKM. Therefore, it is important to all elements in primary school both senior and junior teachers to implement further this Microsoft Sway media in improving online learning.